HUBUNGAN DUKUNGAN SUAMI DENGAN KEMAUAN IBU MEMBERIKAN ASI EKSKLUSIF DI PUSKESMAS TUMINTING KECAMATAN TUMINTING - Abidjulu, Farha Riany; Hutagaol, Esther; Kundre, Rina (Universitas Sam Ratulangi, 2015)
Abstract : Exclusive breastfeeding is given breast milk for 6 months without additional liquids and other foods such as infant formula, banana pulp, and water. According to data from the Health Research in 2013, the percentage of baby who received exclusively breastfed in Indonesia is 54.3%. This is because of the mother’s lack of knowledge, widespread promotion of infant formulas and even the lack of support from family especially husband. This research aimed to determine the relationship of husband’s support with mother’s will for giving exclusively breastfeeding at the Tuminting primary health care in 2014. This is analytical research with cross sectional design, the population of lacting mother’s of infants age ≥ 6 months who came to visit at Tuminting primary health care. This research using purposive sampling technique amounted 61 respondents. The data were collected by distributing questionnaires which is husband’s support questionnaires and mother’s will for giving exclusively breastfeeding. The results of the statistical test using chi square test, the p value = 0.001. This means that the value of p < α (0.05). This it can be concluded that there is a relationship between husband support with mother’s will for giving exclusively breastfeeding. Suggestions for health care, should further improve the education and introduction to the husband’s and lacting mother’s about the importance of husband support for the success of mother’s exclusively breastfeeding. Keywords: Support husband - mother’s will - exclusive breastfeeding. Abstrak : ASI eksklusif adalah ASI yang diberikan selama 6 bulan tanpa tambahan cairan dan makanan lain seperti susu formula, bubur pisang, dan air putih. Menurut data Riset Kesehatan Dasar tahun 2013, presentase bayi yang mendapat ASI eksklusif di Indonesia adalah 54,3%. Kendala ini disebabkan karena kurangnya pengetahuan ibu, maraknya iklan susu formula dan bahkan kurangnya dukungan dari keluarga terlebih suami. Penelitian ini bertujuan untuk mengetahui hubungan dukungan suami dengan kemauan ibu memberikan ASI eksklusif di Puskesmas Tuminting tahun 2014. Desain penelitian yaitu survei analitik dengan rancangan cross sectional, populasi yaitu ibu menyusui bayi usia≥ 6 bulan yang datang berkunjung ke Puskesmas Tuminting. Sampel penelitian ini 61 responden yang didapat dengan menggunakan teknik purposive sampling. Instrumen penelitian yang digunakan berupa kuesioner yang terdiri dari kuesioner dukungan suami dan kemauan ibu memberikan ASI eksklusif. Hasil uji statistik menggunakan uji chi square didapatkan nilai p = 0,001. Ini berarti bahwa nilai p <α (0,05). Dengan demikian dapat disimpulkan bahwa terdapat hubungan antara dukungan suami dengan kemauan ibu memberikan ASI eksklusif.Saran untuk petugas kesehatan agar lebih meningkatkan penyuluhan dan pengenalan kepada para suami dan ibu menyusui tentang pentingnya dukungan suami sehingga mendukung keberhasilan ibu memberikan ASI eksklusif. Kata kunci : Dukungan suami – Kemauan Ibu - ASI eksklusif.